Transcriptome Analysis of MYB Genes and Patterns of Anthocyanin Accumulation During Seed Development in Wheat. (April 2022) - Flores, Paulina Calderon; Yoon, Jin Seok; Kim, Dae Yeon; Seo, Yong Weon
Plants accumulate key metabolites as a response of biotic/abiotic stress conditions. In seed coats, anthocyanins, carotenoids, and chlorophylls can be found. They have been associated as important antioxidants that affect germination. In wheat, anthocyanins can impart the seed coat color which have been recognized as health-promoting nutrients. Transcription factors act as master regulators of cellular processes. Transcription complexes such as MYB-bHLH-WD40 (MBW) regulate the expression of multiple target genes in various plant species. In this study, the spatiotemporal accumulation of seed coat pigments in different developmental stages (10, 20, 30, and 40 days after pollination) was analyzed using cryo-cuts. Moreover, the accumulation of phenolic, anthocyanin, and chlorophyll contents was quantified, and the expression of flavonoid biosynthetic genes was evaluated. Finally, transcriptome analysis was performed to analyze putative MYB genes related to seed coat color, followed by further characterization of putative genes. TaTCL2, an MYB gene, was cloned and sequenced. It was determined that TaTCL2 contains a SANT domain, which is often present in proteins participating in the response to anthocyanin accumulation. Moreover, TaTCL2 transcript levels were shown to be influenced by anthocyanin accumulation during grain development. Interaction network analysis showed interactions with GL2 (HD-ZIP IV), EGL3 (bHLH), and TTG1 (WD40). The findings of this study elucidate the mechanisms underlying color formation in Triticum aestivum L. seed coats.